A New Explanatory Model for Policy Analysis and Evaluation - Marije Schouwstra; Michael Ellman (Tinbergen Institute, 2006)
This model of policy evaluation has been developed to identify factors that cause policy outcomes to diverge from the intended results. In this model the explanatory factors may be inherent to the conceptual and institutional framework to which policy makers adhere, or they may be `real world' factors such as badly-defined performance indicators or cyclical economic problems. This model can be used by scholars for analyzing and evaluating government policies and the policies of international organizations and by policy makers to improve their policies. The model can also be used for cross-country comparisons to establish why a certain policy works in one country or situation and why it does not work in another country or situation.
Keywords: E61; F35; F37; F53; G38; H43; H83; O19; O21; O22; 330; model of policy analysis model of policy evaluation public policy international financial institutions evaluation international organizations cross country comparison policy analysis conceptual framework institutional framework normative formal